2016
DOI: 10.1093/jrr/rrw070
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-ion radiotherapy for locally advanced cervical cancer with bladder invasion

Abstract: The purpose of this study was to evaluate the efficacy and toxicities of carbon-ion radiotherapy (C-ion RT) for locally advanced cervical cancer with bladder invasion by a subset analysis of pooled data from eight prospective clinical trials at the National Institute of Radiological Sciences. Between June 1995 and January 2014, 29 patients with locally advanced cervical cancer with bladder invasion were identified. The median age was 56 years old (range 31–79 years old). The median tumor size at diagnosis on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…CCBI is infrequent and data are scarce, generally showing poor prognosis and high local failure rates. This study with 71 patients, although retrospective, is to date the largest monocentric cohort assessing the clinical outcomes in this population, and one of the first examining prognostic factors associated with VVF [ 15 , 2 , 3 , 16 , 17 ]. Patient prognosis was poor, with median OS and DFS of 27.3 and 15.8 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…CCBI is infrequent and data are scarce, generally showing poor prognosis and high local failure rates. This study with 71 patients, although retrospective, is to date the largest monocentric cohort assessing the clinical outcomes in this population, and one of the first examining prognostic factors associated with VVF [ 15 , 2 , 3 , 16 , 17 ]. Patient prognosis was poor, with median OS and DFS of 27.3 and 15.8 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that 12 C 6þ irradiation has been widely used in the treatment of a variety of cancers, such as pancreatic cancer [11], non-small cell lung cancer [12], locally advanced cervical cancer, prostate carcinoma [13] and breast cancer [14]. What is more, in the stage IVA patients of cervical carcinoma, 12 C 6þ beam radiotherapy has respectively shown a 3-year local control and overall survival rate of 66% and 47%, indicating that it can be applied to locally advanced cervical cancer [15]. Thus far, it is estimated that more than 16,000 patients have received 12 C 6þ treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, Japanese studies showed an excellent efficacy of CIRT with concurrent chemotherapy in women receiving prophylactic extended-field CIRT with higher local control for higher total dose (>70 Gy [relative biological effectiveness [RBE]]) and a better local control rate for large tumors compared with concurrent chemoradiotherapy with photons. Encouraging results were also shown for locally advanced adenocarcinoma [63][64][65][66][67][68][69].…”
Section: The Role Of Particle Radiotherapymentioning
confidence: 96%